G413(P) Problems with the administration of oral formulations to children: Perspectives of medical practitioners, pharmacists and nurses. (7th April 2014) - Venables, RH; Stirling, HF; Marriott, JF
Abstract : Introduction: There is limited evidence regarding healthcare professionals (HCP)s knowledge of issues with medicines administration in paediatric patients with chronic conditions. The few studies that have been conducted have included HCPs working in disease-specific groups 1, 2 and those investigating knowledge on the use of unlicensed medicines. 3, 4 Purpose: The objective was to explore problems with medicines administration in children suffering from chronic conditions from the perspectives of medical practitioners, pharmacists and nurses, and additionally to identify common and unique themes of problems with oral medicines prescribed to children. Materials and methods: Four focus groups (FG) were conducted at two NHS trusts. FG1 (n = 5): neonatal nurse practitioners, nurse practice educator, community paediatric nurses. FG2 (n = 8): GP, general paediatric consultants, specialist paediatric consultants, paediatric registrar. FG3 (n = 2): paediatric pharmacist, specialist pharmacist. FG4 (n = 4): paediatric pharmacists. Themes explored problems experienced when prescribing, dispensing and administering medicines for children. Ethical approval was granted. Results: Themes identified included taste, texture, colour, smell, size/swallowing, quantity/volume and manipulation with food. Taste was the most commonly reported oral-formulation related barrier to medicines administration across the groups. Flucloxacillin solution was discussed with regard to its poor palatability in all groups. Texture was reported to be a significant problem for the learning disability population across the groups. Medicines manipulation techniques (e.g. mixing with foodstuffs) were revealed across the groups, yet there was limited knowledge regarding the evidence base for such activity. Problems surrounding the supply of Specials medicines were discussed in-depth by the pharmacists. Conclusions: Taste was perceived to be the major barrier to medicines administration in children. Further organoleptic and physical properties of medicines were also identified as barriers to medicines administration and should not be overlooked. A robust scientific evidence-base approach is warranted to inform standardised protocols guiding HCPs to support safe and effective medicines manipulation in both domiciliary (i.e. by parents/carers) and hospital (i.e. by nurses) settings. Pharmacists should collaborate with prescribers and provide advice on Specials prescribing owing to their increased knowledge. Findings of this study should help to optimise paediatric prescribing and also direct future formulation work.